Three essays on the discourse and consequences of rural-urban migration in China - Long, Wenjin (2019)
Rural-urban migration in China is the largest human movement in the history of the world in terms of quantity. Rural-urban migrants make great contributions to urban economy and rural development in China. Yet, they usually lack formal supports in both urban and rural areas. The thesis consists of three essays related to rural-urban migration, looking at the discourse and consequences of rural-urban migration in China. The thesis augments the study of migration, social network, and human capital.